Female correctional project and descoloniality. A re-read of the domination project in Córdoba, 1892-1912 (Estudios Sociales, 2022)
This paper is a revision of the female correctional project managed by Buen Pastor’s congregation in Córdoba at the end of XIX century and the beginning of XX century, from a descolonial feminism perspective. Focusing specifically on the wide range of subjectivities that inhabited Cárcel Correccional de Mujeres y Asilo de Menores del Buen Pastor and on correcting strategies, such as job training, I identified relations that allow to spot a gender colonial arrangement that aimed at securing domination and assuring hegemony. Underlying fictions of race, gender and class in this society were identified through the implementation of colocación and weaving of actors that is implied.
Keywords: correctional project; gender coloniality; colocacion